Penerapan Pendekatan Pendidikan Matematika Realistik (PMR) untuk Meningkatkan Hasil Belajar pada Materi Bangun Datar Peserta Didik Kelas V SDN 10 Bandar Buat Kota Padang - Meiliana Fitria Ningrum; Syafri Ahmad (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by the low Mathematics learning outcomes of fifth-grade students of SDN 10 Bandar Buat, Padang City, which is caused by teacher-centered learning and a lack of linking the material to real contexts. This study aims to describe the application of the Realistic Mathematics Education (RMAT) approach in improving learning outcomes on plane geometry material. The study used Classroom Action Research (CAR) which was carried out in two cycles, including the planning, implementation, observation, and reflection stages. The research subjects were 28 fifth-grade students of SDN 10 Bandar Buat, Padang City. Data collection techniques were carried out through observation, interviews, and learning outcome tests. The research instruments were observation sheets for teaching modules, teacher and student activities, and evaluation questions. Data were analyzed qualitatively and quantitatively. The results showed an increase in the quality of learning and student learning outcomes. The average value of learning outcomes increased from 68.33 in cycle I to 84.56 in cycle II. In addition, teacher and student activities also increased with a very good category in cycle II. Based on the research results, it can be concluded that the Realistic Mathematics Education (PMR) approach is able to improve the Mathematics learning outcomes of class V students at SDN 10 Bandar Buat, Padang City.